Un établissement pénitentiaire singulier dans «l’archipel punitif» de l’armée française en Algérie : L’établissement des fers de Douera puis de Bône (1855-1858) - Nadia Biskri (L’Année du Maghreb)
In the spring of 1855, a prison facility for soldiers and sailors sentenced to chains was set up in Algeria, in the Douera military camp and then in the fortress of Bône. Its creation resulted from the Second Empire’s penitentiary policy based on the settlement of undesirables in the colonies, at a remove from the metropolis. Although these centers of detention did not last more than three years, this place of punishment for deviants to the military order has proven for the historian to be a real observatory of a penitentiary experiment in a colonial situation. Unique among the punitive structures of the French army in Algeria, the establishment of chain imprisonment in Douera / Bône, testifies to the permeability of the civil and military prison systems in a context of sharp conflict of competences between military and civil authorities. Prison discourse and practices regarding those sentenced to chains allow us to grasp the double punitive and penitential conception of prison as punishment as much as rehabilitation of degraded servicemen while serving the interests of colonization through forced labor.